Assessment of Physical and Emotional Status and Fear among Women with Breast Cancer in Mosul City: physical, emotional status and fear - Mukhlif, Hanaa Hussein (Iraqi Journal of Cancer and Medical Genetics, 2025)
Breast cancer is a significant health issue that affects patients› physical, emotional, and financial well-being as well as the health of their families. This study aimed to assess the physical, emotional, and fear of women with breast cancer. A descriptive cross-sectional study was carried out from November 2023 until July 2024. Ninety patients were selected from a purposive sample taken from the Nuclear Medicine Oncology Hospital in Mosul City. The study instrument includes questions about demographic and clinical data, physical and emotional health, and fear. Three response alternatives for each item (always, sometimes, never). Both descriptive and inferential statistics, such as chi-square tests, were used to examine the data, and the reliability estimate of the questionnaire was 0.89 breast cancer in women between the ages of 40 and 49 years. The affected women›s physical and emotional states were moderately impacted (46.7% and 51.5%, respectively). The responses from the participants indicated that their level of fear was between moderate and high. Additionally, there are worries about the disease›s potential to manifest and spread throughout the body.  The study recommends that cancer patients benefit from good physical and emotional support to enhance their health, reduce their worry and fear through the use of coping strategies.